A Renal Function Based Trade-Off Analysis of Non-vitamin K Antagonist Oral Anticoagulants in Nonvalvular Atrial Fibrillation - Zhou, Ling-Yun; Yang, Shuo-Fei; Zhang, Zhen; Zhang, Chi; Shen, Long; Gu, Zhi-Chun; Zuo, Xiao-Cong (Frontiers in Physiology, 2018)
Background: Non-vitamin K antagonist oral anticoagulants (NOACs) depend on some degree of renal excretion, and no head-to-head comparisons based on renal function is available. This study mainly investigated the trade-off property of NOACs in nonvalvular atrial fibrillation (NVAF) with varying degrees of renal function. Methods: A comprehensive search of Medline, Embase, Cochrane Library, and Clinical Trials.gov Website was performed for eligible randomized controlled trials (RCTs) that reported the efficacy and safety outcomes according to renal function of NOACs. Primary efficacy outcome was any Stroke or systemic embolism (S/SE). Major bleeding was considered as a primary safety outcome. Risk ratios (RRs) with their confidence intervals (CIs), the surface under the cumulative ranking curve (SUCRA), and trade-off analysis were conducted by renal function. Results: Finally, 5 phase III Clinical Trials (72961 NVAF patients) comparing NOACs with warfarin in NVAF patients were included. In terms of normal renal function, dabigatran-150 mg was ranked first for efficacy (SUCRA: 90.3), and edoxaban-30 mg was ranked first for safety (SUCRA: 93.3). Dabigatran-110 mg/150 mg, and apixaban-5 mg were regarded as the most effective and reasonably safe interventions in the trade-off analysis. Regarding mild renal impairment, edoxaban-60 mg was ranked first for efficacy (SUCRA: 97.8), and edoxaban-30 mg was ranked first for safety (SUCRA: 99.5). Edoxaban-60 mg and dabigatran-150 mg were accounted as the most effective and reasonably safe interventions. With regards to moderate renal impairment, dabigatran-150 mg was ranked first for efficacy (SUCRA: 95.1), and edoxaban-15 mg was ranked first for safety (SUCRA: 98.2). Apixaban-2.5 mg and Edoxaban-30 mg was considered as the reasonably effective and the safest interventions. Conclusions: Dabigatran-150 mg seems the most effective therapy in patients with normal renal function and moderate renal impairment, and edoxaban-60 mg in patients with mild renal impairment. Low dose edoxaban (15 and 30 mg) seems the safest intervention. Apixaban-2.5 mg and edoxaban-30 mg might be the best trade-off property in moderate renal insufficiency. HIGHLIGHTS Dabigatran-150 mg seems the most effective therapy for normal renal function and moderate renal impairment patients, edoxaban-60 mg for mild renal impairment patients. Low-dose edoxaban can be considered as a good choice in NVAF patients at high risk of bleeding. Apixaban-2.5 mg and edoxaban-30 mg might be the balanced option in NVAF patients with moderate renal insufficiency. STUDY REGISTRATION: PROSPERO Identifier, CRD42017054235.